2020
DOI: 10.1186/s40001-020-00454-x
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the impact of COVID-19 on liver dysfunction

Abstract: Background The novel coronavirus disease 2019 (COVID-19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is leading to a worldwide pandemic. Except representative manifestation of pneumonia and acute respiratory symptoms, COVID-19 patients have also shown different levels of liver injury or liver dysfunction. The aim of our study was to explore the probable clinical severity and mortality of COVID-19 patients and their liver dysfunction. Method A combination of computer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 27 publications
4
67
0
Order By: Relevance
“…In support, intra-gastric inoculation of SARS-CoV-2 in a mouse model expressing human ACE2 caused productive infection and most interestingly led to pulmonary pathological changes [40]. A significant association between liver dysfunction and mortality of COVID-19 patients has been also reported [41,42], which may vasodilation, increased capillary permeability, apoptosis/necrosis of endothelial cells as well as 12. ARDS-induced "cytokine storm" and likely virus entry to the circulation which may then cause systemic failure due to broad organotropism in tissues expressing high levels of ACE2 (e.g., heart and kidneys) or the "cytokine storm"-related excessive inflammation, are indicated.…”
Section: The Critically Balanced Ace/angii/at1r and Ace2/ Ang(1-7)/mamentioning
confidence: 86%
See 1 more Smart Citation
“…In support, intra-gastric inoculation of SARS-CoV-2 in a mouse model expressing human ACE2 caused productive infection and most interestingly led to pulmonary pathological changes [40]. A significant association between liver dysfunction and mortality of COVID-19 patients has been also reported [41,42], which may vasodilation, increased capillary permeability, apoptosis/necrosis of endothelial cells as well as 12. ARDS-induced "cytokine storm" and likely virus entry to the circulation which may then cause systemic failure due to broad organotropism in tissues expressing high levels of ACE2 (e.g., heart and kidneys) or the "cytokine storm"-related excessive inflammation, are indicated.…”
Section: The Critically Balanced Ace/angii/at1r and Ace2/ Ang(1-7)/mamentioning
confidence: 86%
“…In support, intra-gastric inoculation of SARS-CoV-2 in a mouse model expressing human ACE2 caused productive infection and most interestingly led to pulmonary pathological changes [ 40 ]. A significant association between liver dysfunction and mortality of COVID-19 patients has been also reported [ 41 , 42 ], which may relate to direct viral infection (still questionable due to relatively low ACE2 expression levels in the liver [ 17 ]); to indirect damage because of drug-induced liver injury or because of COVID-19-triggered systemic inflammation [ 43 ]. Analyses of severe COVID-19-induced biochemical alterations in the liver have shown the elevation of liver enzymes, such as alanine aminotransferases and aspartate aminotransferases, and significantly lower albumin levels [ 43 , 44 ] and thus, liver markers should be monitored continuously during COVID-19 evolvement.…”
Section: The Critically Balanced Ace/angii/at1r and Ace2/ang(1–7)/masmentioning
confidence: 99%
“… 10 A meta-analysis proved that there was a relationship between liver injury and severity and mortality of patients with COVID-19. 11 However, Wang et al 9 reported there were no differences in ALT between survival and death, and argued that although liver injury was common in patients with infectious SARS-Cov-2, abnormal liver functioning may not a notable symptom of COVID-19 disease. Our study found that AST on admission and at its peak was higher in critical patients than the other two groups, suggesting that AST was associated with disease severity; however, ALT on admission showed no difference among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…26 The prevalence of aspartate aminotransferase (AST) elevation ranged between 4% to 53% in a Chinese cohort and up to 58% in a USA cohort. 23,25,26 Both enzymes were mildly elevated in terms of absolute numbers and less than 5-times the upper limit of normal (ULN) in the majority. Kulkarni et al 13 in their meta-analysis, placed the pooled incidence of AST and ALT elevation at 22.5% and 20.1%, respectively.…”
Section: Liver Function Test Abnormalitiesmentioning
confidence: 99%
“…Alanine aminotransferase (ALT) elevations were seen in 4% to 33% of cases, according to China's initial reports, [23][24][25] and 39% of cases in a large study from New York, USA. 26 The prevalence of aspartate aminotransferase (AST) elevation ranged between 4% to 53% in a Chinese cohort and up to 58% in a USA cohort.…”
Section: Liver Function Test Abnormalitiesmentioning
confidence: 99%